The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/02783649231201196
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic movement primitives in robotics: A tutorial survey

Matteo Saveriano,
Fares J Abu-Dakka,
Aljaž Kramberger
et al.

Abstract: Biological systems, including human beings, have the innate ability to perform complex tasks in a versatile and agile manner. Researchers in sensorimotor control have aimed to comprehend and formally define this innate characteristic. The idea, supported by several experimental findings, that biological systems are able to combine and adapt basic units of motion into complex tasks finally leads to the formulation of the motor primitives’ theory. In this respect, Dynamic Movement Primitives (DMPs) represent an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 372 publications
0
15
0
Order By: Relevance
“…Through investigating previous works (Ijspeert et al , 2013; Lu et al , 2021; Saveriano et al , 2021), we found that the real-time status of the robot and the relative position relationship of the workspace can be used to design additional terms and achieve the desired functionality through these additional terms. They can be summarized in the following abstract form: here, ϕ ( s , τ ) represents “canonical system” similar to equation (4), f 2 ( g , x , v , τ ) represents K ( g − x ) − Dv in (1), u ( g , x 0 , s , τ ) represents a forcing term similar to equation (3), Δ u and Δ v , respectively, represent additional acceleration terms and additional velocity terms for achieving the desired functionality.…”
Section: Methods Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Through investigating previous works (Ijspeert et al , 2013; Lu et al , 2021; Saveriano et al , 2021), we found that the real-time status of the robot and the relative position relationship of the workspace can be used to design additional terms and achieve the desired functionality through these additional terms. They can be summarized in the following abstract form: here, ϕ ( s , τ ) represents “canonical system” similar to equation (4), f 2 ( g , x , v , τ ) represents K ( g − x ) − Dv in (1), u ( g , x 0 , s , τ ) represents a forcing term similar to equation (3), Δ u and Δ v , respectively, represent additional acceleration terms and additional velocity terms for achieving the desired functionality.…”
Section: Methods Designmentioning
confidence: 99%
“…In this section, we introduce the process of motion skill learning and generalization based on EC-DMPs. Similar to the general skill learning process based on DMPs (Saveriano et al , 2021), the entire process can be divided into two stages: skill learning and skill generalization. In the learning stage, a reference task is first given, and a parameterized primitive sequence is obtained through task decomposition (Da Silva et al , 2012).…”
Section: Methods Designmentioning
confidence: 99%
“…Here, we provide a short demonstration about the convergence and stability of the proposed frame, with respect to reference [21]. Theorem With the consideration of the manipulator system, integrated with the force tracking error constraints framework and adaptive DMPs, the proposed scheme guarantee the stability of DMPs and convergency to target point .…”
Section: Modified Dmps For Force Constraintsmentioning
confidence: 97%
“…Previous researches illustrate that a safe interaction can also be achieved by developing an online adaptive motion generation scheme. The conventional dynamic movement primitive (DMP) framework is developed by introducing a coupling term to improve the limitation while tackling the problems of assembly, trajectory planning, obstacle avoidance, etc [21, 22]. Afterwards, various researches attempted to take the force and stiffness information into account while designing a modified DMPs [23–25].…”
Section: Introductionmentioning
confidence: 99%
“…Within the field of robotics, dynamic movement primitives (DMP) refers to a commonly applied imitative motion planning method. [ 17,18 ] Similar to APF, DMP encodes obstacles as PFs to generate repulsive effects, while it differs from traditional APF in that the attractive effect is encoded using local targets and human demonstrations. DMP encodes the target and demonstration with a succession or concurrent execution of primitive movement.…”
Section: Introductionmentioning
confidence: 99%